Food businesses and export requirements: a first glance at current perception and future expectations - Andrea Gori; Andrea Armani; Lara Tinacci; Pietro Noè; Nicola Santini; Daniele Tognetti; Roberta Nuvoloni (Italian Journal of Food Safety)
The export of agri-food products represents a pillar of the Italian economy. However, food businesses (FBs) must comply with a series of requirements, including those imposed by importing countries. This study conducted in-depth interviews with three Italian FBs producing food of animal origin to explore their perception about procedures, documentation, and the role of the central competent authority (CA) related to export. Interviews with food quality managers (FQMs) (February-April 2024) revealed similar challenges across different sectors, particularly regarding the availability and clarity of information. FQMs suggested the implementation of a centralized online platform to enhance access to necessary information. Additionally, the study revealed a lack of full awareness among FQMs about central CA’s role in the export process. A coordinated approach involving central, regional, and local CAs, trade associations, and the productive sector could be crucial to ensure the success of FBs in the international market.